Insecticidal Effects of Native Raw and Commercial Diatomaceous Earth Against Lesser Grain Borer and Granary Weevil Under Different Environmental Conditions - Ogreten, Ayhan; Eren, Sedat; Mutlu, Cetin; Ayaz, Tarkan; Saeed, Amna; Bingham, Georgina V.; Morrison, William R. (Mdpi, 2025)
Stored grain pests cause significant economic losses during cereal grain storage. Insecticides have long been central to pest control; however, growing concerns over resistance, environmental harm, and human health demand alternative strategies. Diatomaceous earth (DE) treatments are a safe, eco-friendly alternative to insecticides, although their efficacy depends on the temperature, humidity, dose, and insect species. This study assessed the insecticidal effects of two natively-sourced raw (Ankara and Aydin) and one commercial (Silico-Sec) DE treatments against the key pest species Rhyzopertha dominica (F.) and Sitophilus granarius (L.) on stored wheat. Five doses (0, 250, 500, 750, and 1000 ppm) of each DE treatment were tested under two temperatures (25 degrees C and 30 degrees C) and two humidity levels (40% and 60%). Mortality was assessed at 7, 14, and 21 days after treatment (DAT). All DE treatments caused higher mortality in S. granarius than R. dominica. The highest mortality occurred in S. granarius at 30 degrees C and 40% RH with the highest dose. Aydin DE was most effective, but did not reach 100% mortality in S. granarius by 21 DAT. In contrast, it caused 100% mortality in R. dominica under the same conditions. There was no F1 progeny produced by surviving individuals of both species. Given the similarity of the environmental conditions to the optimal conditions for DE efficacy present in Turkish storage facilities, natively sourced Aydin DE is a promising control option.
Keywords: Rhyzopertha dominica; Sitophilus granarius; diatomaceous earth; IPM; storage pests